A study of acute pesticide poisoning in a tertiary care centre in South India - Bommineni, Sashidhar Reddy; Alekhya, K.; Chary, Rallabandi Penta; Reddy, Sai Bhargav; Sahithi (International Journal of Research in Medical Sciences, 2024)
Background: Poisoning has been one of the common cause for mortality. According to WHO the incidence of poisoning has been increased. Poisoning can either be accidental exposure or suicidal in nature. In India pesticides are commonly used poisoning agents for suicide. This present study aimed to assess the incidence and outcome of acute poisoning presenting to our institute. Methods: The study was conducted at RVMIMS for a period of one year from 2023-2024 in the deprtment of General Medicine. Retrospective data of the patients admitted with history of pesticide poisoning was collected and analysed. All patients who gave consent and >14 years were included in the study. Exclusion criteria were age <14 years, pregnant and lactating women and corrosive poisoning. Results: Insecticide poisoning (53.6%) and herbicide poisoning (38.1%) were found to have high incidence. OP ompound is the most common poisoning out of the total cases studied which were 300. Male to female ratio was 3:2. Mortality rate is high due to paraquat poisoning (76.5%) and OP compound (17.6%) poisoning. Methemoglobinemia was seen in patients with plant protector poisoning. Conclusions: We observed that in OP compound poisonings, early intubation with mechanical ventilator support in patients with very low serum pseudocholinesterase patients have good outcome.